The Evaluation of Physical Education, Sport, and Exercise for Individuals with Mental Disabilities in Turkey: A Study of Meta-Synthesis - Bastik, Canan; Gumusdag, Hayrettin; Cetiner, Omurhan; Gursoy, Recep; Ozmaden, Murat (Progress in Nutrition, 2021)
Study Objectives: This study aimed to analyze the results of studies conducted on physical education, sports, exercise, and physical activity applied to individuals with developmental disabilities in Turkey. Methods: A total of 47 studies, including 23 master theses between 2012-2020 and 24 articles between 2014-2020 were examined, and the obtained data were analyzed with a meta-synthesis study using the qualitative research method. Studies to be included in the research were chosen by using the Google Academic search engine, Council of Higher Education National Thesis Center, and Dergipark databases. Chosen articles’ code, author, year and aim, distribution by type, data collection tools, sample group, and sample number, research methods, and the data related to the results obtained at the end of these studies were examined in detail. However, in this study, a general evaluation of existing studies in the literature was performed. Results: It was predicted that the data obtained would be beneficial in terms of directing future research and in terms of awareness of physical education, sports, exercise, and physical activity studies conducted for individuals with mental disability. Conclusion: It was determined that when physical education, sports, and exercises applied to individuals with mental disabilities at a trainable level systematically and regularly, provided positive and significant improvements on their bio motor properties.